Замена:
Получаем уравнение:
D=
t₁=
t₂=
Обратная замена:
1=
x(x+1)=0
x₁=0
x₂=-1
-3=
D= - нет решений.
ответ: -1; 0.
Замена:
Получаем уравнение:
D=![b^{2} -4ac=2^{2} -4*1*(-3)=4+12=16](/tpl/images/0989/1652/7e751.png)
t₁=![\frac{-b+\sqrt{D} }{2a}= \frac{-2+4}{2} = 1](/tpl/images/0989/1652/3585f.png)
t₂=![\frac{-b-\sqrt{D} }{2a}= \frac{-2-4}{2} = -3](/tpl/images/0989/1652/46c38.png)
Обратная замена:
1=![x^{2}+x-1](/tpl/images/0989/1652/6a82d.png)
x(x+1)=0
x₁=0
x₂=-1
-3=![x^{2}+x-1](/tpl/images/0989/1652/6a82d.png)
D=
- нет решений.
ответ: -1; 0.